The Relation of Tests of Scientific Reasoning to Each Other and to Tests of General Intelligence - Sternberg, Robert J. (J Intell, 2019)
We conducted two studies to replicate and extend, as well as test, the limits of previous findings regarding an apparent disconnect between scientific-reasoning skills in psychological science, on the one hand, and scores on standardized tests of general intelligence, on the other. In Study 1, we examined whether this disconnect would extend beyond psychological science to additional sciences as well, such as nutrition and agriculture. The results did indeed extend, suggesting that scientific reasoning across various natural sciences is comparable to scientific reasoning in psychological science, but different in kind from the reasoning required on conventional standardized tests. In Study 2, we examined whether these findings were linked to the format of presentation of scientific problems. Whereas real scientific-reasoning problems are open-ended, standardized tests tend to use multiple-choice format. We discovered that using multiple-choice format did indeed result in an apparently closer relation of the scientific-reasoning tests to two of the conventional ability measures (SAT Reading and Number Series) but not to two other tests (Letter Sets and SAT Math). Thus, one can increase the correlations of scientific-reasoning tests with at least some standardized ability tests but at the cost of content validity and ecological validity.